Economic evaluation of a bio-psycho-social intervention for comorbid disorders in a traumatized population in post-war Kosovo - Wei-Lun Chang; Carit Jacques Andersen; Besa Shatri Berisha; Olena Estrup; Shr-Jie Wang (Medical Journals Sweden, 2018)
Objective: Post-hoc economic evaluation of a bio-psycho-social intervention in post-war Kosovo from a societal perspective. Design: Cost-effectiveness analysis, cost-utility analysis, and partial cost-benefit analysis using data from a randomized controlled trial. Patients: Thirty-four torture/war victims with comorbid conditions enrolled in 2012-2013. Methods: Participants were randomly assigned to an "intervention" and a "waiting-list" group. Changes in mental, emotional and physical health and functional impairment were assessed before and after treatment, along with increase in labour income as a proxy for productivity gain. The cost of an extra unit of effectiveness and an additional quality-adjusted life year were calculated. Results: The total cost per participant was €1,322 including, or €1,019 excluding, research costs. Wide variations in costs of changes in mental, emotional and physical effectiveness were demonstrated. Multidisciplinary intervention resulted in functional improvement at a cost of €10,508 per quality-adjusted life year gained. With a mean monthly income increase to €133 (18%) after intervention, the intervention cost per participant would be equal to the total increase in monthly income after 4-5 years, assuming the increased level is maintained. Conclusion: Socio-economic benefit associated with quality-adjusted life year gain is shown, although the cost of an additional quality-adjusted life year is above the World Health Organization cost-effectiveness threshold.